Electrical conduction in carbon-ion implanted diamond and other materials at low temperatures. - Tshepe, Tshakane Frans (My University, 1992)
The role of intersite electron correlation effects and the possible occurrence of the metal-insulator transition in carbon-ion implanted type IIa diamond samples have been studied at very low temperatures, using four- and two-point probe contact electrical conductivity measuring techniques. The measurements were extended to ruthenium oxide thin films in the presence and absence of a constant magnetic field of B = 4.0 T down to 100 mK, using a 3He-4He dilution refrigerator. The effect of the Coulomb gap in the variable range hopping regime has been well studied by other workers. The results tend to follow the Efros-Shklovskii behaviour with a trend towards the Mott T- 114 law for diamond samples far removed from the metal insulator transition, on the insulating side at low temperatures.
A research report submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science
Keywords: Electric conductivity.; Ion implantation.; Carbon compounds.; Materials at low temperatures.